Mapping current literary research on textual space and space texts (KULT_online, 2016)
The Handbook to Literature & Space (Handbuch Literatur & Raum) provides an innovative guide to the field of interdisciplinary literary research on textual spaces and space texts. Following up-to-date research questions, the handbook offers comprehensible texts which are nevertheless informative and written densely. Single entries have been interlinked extensively. Exemplary analyses of primary texts are illustrated by specific recourse to the canonical texts of spatial theory. The book therefore offers insight especially into current research on space in literary studies.